Women’s Strength in the Film: An Interpersonal Analysis - Ramadhanti, Kyla Putri; Salsabila, Prina Naura; Alifia, Dinda Nabilla (Nexus Publishing, 2024)
In this study, a woman who strives to uphold her honor and emphasizes feminism is the main subject and is shown over the course of four acts. The acts are titled